Maltreatment (psychological, physical), social physique anxiety, body dissatification and drive for thinness in Greek female athletes (rhythmic gymnastics and other sports) after dropout - Kosmidou, E.; Giannitsopoulou, E.; Kountouratzi, N.; Karatzioti, M. (Science of Gymnastics Journal, 2022)
Maltreatment by coaches is a significant issue for all athletes, and particularly female athletes. The purpose of the present study was to examine whether psychological and physical maltreatment by coaches could affect social physique anxiety, body dissatisfaction and drive for thinness in former Greek female athletes. Two hundred and fifty former athletes participated in the study, former athletes in rrhythmic gymnastics (RG) and other sports (OS). They completed self-reported questionnaires assessing maltreatment (psychological, physical) by coaches, social physique anxiety, body dissatisfaction and drive for thinness. Results revealed that RG reported both higher psychological and physical maltreatment than others, but there were no differences in body dissatisfaction, drive for thinness and social physique anxiety. Although there were significant relations between maltreatment and body dissatisfaction, and drive for thinness, it was predictive for other sports athletes and not RG athletes. These findings can potentially help all types of sports become a context that promotes female athletes` health rather than undermines it.